Impacts of necrosis mite on the development of hybrid coconut fruits in commercial planting (Research, Society and Development, 2021)
The study aimed to analyze the main impacts caused by the necrosis mite on hybrid coconuts in a commercial coconut plantation, in addition to verifying which hybrid is the most resistant to damage caused by the pest. For this purpose, the collections were carried out in a commercial plantation in plots sub-divided in space and time. During the research, the weight of the solid albumen, the volume of liquid albumen and the damage severity in the fiber of 1920 coconuts were analyzed in the Assistat software, divided into three levels of damage. The results showed that the hybrid coconut identified by PB-123 showed greater weight of solid albumen, greater volume of liquid albumen and less severity of damage to the fiber, therefore, this hybrid was identified as the most resistant to attacks by this pest. Taking into account the rain as a limiting factor for the pest, it was noted that the collected coconuts developed significantly better in the periods of initial growth with higher rainfall. With these data, it is possible to give special attention to the PB-123 hybrid in future plantations, characterizing it as the most resistant hybrid to damage caused by the mite. In addition to reaffirming that the mite that causes necrosis is easy to disperse and causes profound damage to coconut fruit, which may be associated with loss of commercial value for its producers.